Alat Penilaian Hasil Belajar Siswa Sekolah Dasar Berdasarkan Kurikulum 2013 di SDN Gandasari 1 - Azis, Jumratul Aqabah; Setyani, Gading Retna Tri; Urfa, Salsa Rojana; Cahyani, Septia Putri (TSAQOFAH, 2022)
This study aims "To describe the Learning Outcomes Assessment Tool for Elementary School Students Based on the 2013 Curriculum". The approach used in this research is a qualitative approach. With the intention of this qualitative research is a research process that produces descriptive data. The type of research used is an Elementary School Student Learning Outcome Assessment Tool Based on the 2013 Curriculum. In general, the learning outcomes assessment tool is divided into two criteria, namely test-based assessment and non-test assessment. Tests are generally used to assess and measure student learning outcomes, especially cognitive learning outcomes with regard to mastery of teaching materials in accordance with educational and teaching objectives. researcher questions. with interview techniques. Based on interviews conducted at the Gandasari 1 State Elementary School, it can be concluded that the assessment is knowledge or cognitive in nature if in K13 it is divided into three domains, namely the domain of attitudes, the realm of knowledge, and the realm of skills. The sources can be from daily tests, mid-semester tests, and end-of-semester tests. So the three were combined and then accumulated continuously in the amount divided into the report card value.